INTERNATIONAL STANDARDS FOR COMBATING TORTURE AND THEIR IMPLEMENTATION IN THE LEGISLATION OF CENTRAL ASIAN COUNTRIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article provides an analytical overview of international obligations to prevent torture (the 1984 UN Convention against Torture and its Optional Protocol), as well as the status of their implementation in the legislation and practice of Kazakhstan, Kyrgyzstan and Uzbekistan. The current national mechanisms (e.g., national preventive mechanisms – NPMs), problems of enforcement, judicial practice and control are considered. Regional examples (UN, OSCE, Amnesty Academy) and a comparative table of articles on torture (article of the Criminal Code, sanctions, monitoring, execution) are given. Ethical aspects (transparency, rights of detainees, access to a lawyer) are analyzed separately and practical recommendations are given (strengthening NPM, police training, independent supervision, open statistics). For the first time, key performance indicators (KPIs) for the implementation of standards (number of complaints, investigations, convicted of torture, visits to places of detention, etc.) have been formulated to assess progress in the fight against torture. A diagram (Mermaid) of the torture complaint review process from filing to court decision is presented.
Keywords: torture, international standards, national preventive mechanism, UN, Convention against Torture, OSCE, criminal procedure